2009
DOI: 10.1111/j.1467-9221.2009.00732.x
|View full text |Cite
|
Sign up to set email alerts
|

Six Factors Fostering Protest: Predicting Participation in Locally Unwanted Land Uses Movements

Abstract: In two studies we analyzed the predictors of participation in an Italian Lulu mobilization, rooted in the Susa Valley, a North-Western Italian valley where a high speed railway (HSR) should be sited. Based on the data of qualitative Study 1, performed interviewing 12 anti-HSR militants and 12 non anti-HSR militants, we hypothesized that Klandermans' (1997) model on participation (centered on group identification, sense of injustice, and collective efficacy) is suitable to predict the Lulu mobilization we studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 55 publications
2
61
0
4
Order By: Relevance
“…These approaches proved to be the most effective at managing the NIMBY conflicts (McAvoy, 1998). However, the conflicts were never presented as arising, at least in part, from psychological ties between opponents and their communities (Mannarini et al 2009). Thus, they were never represented as specific forms of place-protective actions, which arise when individuals perceive relevant environmental changes as threats to their place identity and as generating disruption in social and psychological bonds between individuals and their community (Devine-Wright 2009, Garavan 2007.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These approaches proved to be the most effective at managing the NIMBY conflicts (McAvoy, 1998). However, the conflicts were never presented as arising, at least in part, from psychological ties between opponents and their communities (Mannarini et al 2009). Thus, they were never represented as specific forms of place-protective actions, which arise when individuals perceive relevant environmental changes as threats to their place identity and as generating disruption in social and psychological bonds between individuals and their community (Devine-Wright 2009, Garavan 2007.…”
Section: Discussionmentioning
confidence: 99%
“…This cognitive distortion is consistent with two families of results from studies done on intergroup relations. Firstly, research on ingroup overexclusion (Yzerbyt et al 1995) showed that individuals who strongly identify with their ingroup, which is systematically the case among the local opponents (Mannarini et al, 2009), tend to be cautious when deciding whether an individual belongs to their ingroup or not. Due to their strong motivation to avoid erroneously "contaminating" their ingroup by including outgroup members, they prefer to risk a "false negative" to a "false positive" mistake.…”
Section: Discussionmentioning
confidence: 99%
“…Questions relating to political and social themes were based on previous studies that identified a sense of injustice and efficacy as cornerstones of collective action (Mannarini et al 2009). Place-related questions were based on the framework developed by Scannel and Gifford (2010), from which we selected the items that were most salient in the informal http://www.ecologyandsociety.org/vol17/iss1/art33/ interviews conducted in the field (FN, 1-23 October 2009); for instance, the themes of pride and personal history-also reported elsewhere as major components of place attachment in Italy (Carrus et al 2005).…”
Section: Questionnairementioning
confidence: 99%
“…Emotions are pervasive in the relationships people have with their local environments (see also Mitchell et al 1993), and these can be pivotal when it comes to environmental planning: able, for instance, to trigger a social movement (see also Heatherington 2005, Devine-Wright 2009, and Mannarini et al 2009). The defense of one's identity plays an important role in the emergence of social movements (Poletta and Jasper 2001), and this is true for place-defense movements.…”
Section: Engaging the Public Around Place Attachments And Meaningsmentioning
confidence: 99%
“…Moreover, these kinds of problems do not remain restricted to wind power. Local acceptance of all types of infrastructure facilities is steeped in local conflict (83) and infrastructures that aim to further environmental policy targets, such as environmentally benign waste management and climate change adaptation or mitigation are no exceptions (84). The roots of these conflicts are complex as they always combine opposing interests regarding the use of the facility and the burden of the facility in terms of local social or environmental impact.…”
Section: Two Dimensions Of Community Involvementmentioning
confidence: 99%